2017
DOI: 10.3389/fmars.2017.00029
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Dynamic Benthic-Pelagic Coupling and Feedbacks in a Coastal Upwelling System (Peruvian Shelf)

Abstract: Monthly time-series data (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) of bottom water oxygen, nitrate and nitrite concentrations from the outer shelf (150 m water depth) in the oxygen minimum zone offshore Peru were coupled to a layered biogeochemical sediment model to investigate benthic-pelagic coupling over multi-annual time scales. The model includes the mineralization of four reactive pools of particulate organic carbon (POC) with lifetimes of 0.13, 1.3, 20, and 1700 year that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 68 publications
(129 reference statements)
2
33
0
1
Order By: Relevance
“…The significant effect on denitrification in the eastern South Pacific Ocean due to changes in the equatorial winds during El Niño was previously described by Codispoti et al (1988). On the continental shelf off the coast of Callao, Dale et al (2017) showed the occurrence of intraannual and interannual variability in the denitrification and anammox processes that appears to decrease under El Niño coupled with low primary productivity and high bottom water oxygenation. In contrast, between 1999 and 2001, Ndef of 40 µmol L −1 peaked under a shallow and well-developed OMZ (Fig.…”
Section: Dissolved Oxygenmentioning
confidence: 58%
See 1 more Smart Citation
“…The significant effect on denitrification in the eastern South Pacific Ocean due to changes in the equatorial winds during El Niño was previously described by Codispoti et al (1988). On the continental shelf off the coast of Callao, Dale et al (2017) showed the occurrence of intraannual and interannual variability in the denitrification and anammox processes that appears to decrease under El Niño coupled with low primary productivity and high bottom water oxygenation. In contrast, between 1999 and 2001, Ndef of 40 µmol L −1 peaked under a shallow and well-developed OMZ (Fig.…”
Section: Dissolved Oxygenmentioning
confidence: 58%
“…The OMZ variability in terms of distribution and intensity has a direct impact on the biogeochemical processes of the northern region of the Humboldt upwelling system because oxygen (1) is a key factor in biogeochemical cycles, particularly in the carbon (Friederich et al, 2008) and nitrogen processes (e.g., Kock et al, 2016;Hammersley et al, 2007;Lam and Kuypers, 2011;Dale et al, 2017). (2) Its consumption determines high nitrogen loss and in consequence a low N : P ratio of upwelled waters, below the classical Redfield ratio of 16, with a strong impact on primary and secondary production (Franz et al, 2012), and (3) it is a control factor in the distribution of organisms (e.g., Bertrand et al, 2010;Criales-Hernández et al, 2006;Ekau et al, 2010;Gutiérrez et al, 2008;Levin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because microbial storage of nitrate and nitrite by microorganisms in the sediment can sustain vigorous N turnover even in the absence of bottom water nitrate and nitrite Sommer et al, 2016), episodic events of 435 nitrogen supply can be associated with continuous benthic nitrogen cycling. The absence of nitrate supply due the absence of CTWs over longer time periods favours the depletion of nitrate in the water column as observed by Sommer et al (2016) and may lead ultimately to the development of sulfidic events (Schunck et al, 2013;Dale et al, 2017;Callbeck et al, 2018).…”
Section: Summary and Discussion 345mentioning
confidence: 98%
“…Enhanced preservation of labile organic matter in anoxic sediments 16 fuels an intricate network of microbe-mediated anaerobic processes such as organic compounds fermentation, methanogenesis/methanotrophy, sulfate reduction and sulfide oxidation 23 26 . However, compared to the other major OMZs of the world 27 32 relatively less information is available on the sediment carbon-sulfur biogeochemistry of the Arabian Sea (moreover, most of the latter studies are centered off the Oman and Pakistan margins) 24 , 33 36 . So far as the overall geomicrobiology of Arabian Sea OMZ sediments are concerned, apart from few recent studies on reflection of climatic oscillation within the microbiome 37 and microbial characterization coupled with enzymatic diversity 38 , such studies are rare that integrate solid-phase/pore-fluid chemistry with comprehensive microbial diversity data obtained using high-throughput metagenomics.…”
Section: Introductionmentioning
confidence: 99%